Neurotensin receptor 1 agonist provides neuroprotection in pre-diabetic rats. Issue 1 (January 2021) - Saiyasit, Napatsorn; Chunchai, Titikorn; Jaiwongkam, Thidarat; Kerdphoo, Sasiwan; Apaijai, Nattayaporn; Pratchayasakul, Wasana; Sripetchwandee, Jirapas; Chattipakorn, Nipon; Chattipakorn, Siriporn C
Abstract : Exogenous treatment of a neurotensin receptor 1 (NTR1) agonist exerted the neuroprotection in an obese and Alzheimer's model. However, the effects of NTR1 modulation on peripheral/hippocampal impairment and cognitive deficit following sustained HFD consumption are poorly understood. Forty rats received a normal diet (ND) or HFD for 16 weeks. At week 13, the ND group received a vehicle ( n = 8). Thirty-two HFD-fed group were randomized into four subgroups ( n = 8/subgroup) with a vehicle, 1 mg/kg of NTR1 agonist, 1 mg/kg of NTR antagonist, and combined treatment (NTR1 agonist-NTR antagonist) for 2 weeks, s.c. injection. Then, the cognitive tests and peripheral/hippocampal parameters were determined. Our findings demonstrated that NTR1 activator reversed obesity and attenuated metabolic impairment in pre-diabetic rats. It also alleviated hippocampal pathologies and synaptic dysplasticity, leading to deceleration or prevention of cognitive impairment progression. Therefore, NTR1 activation would be a possible novel therapy to decelerate or prevent progression of neuropathology and cognitive impairment in the pre-diabetes.